TEKNOLOGI PROSES PEMBUATAN ALAT PENGUPAS KULIT KACANG MERAH DENGAN DUAL ROLL PENGUPAS KAPASITAS 100 KG/JAM - Ginting, Fajar Kerehen Yusuf; Mahyunis, Mahyunis; Mahadi, Batu (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2017)
Red bean skin peeler machine with a capacity of 100 kg / hour using dual roll peeler is a tool to facilitate the public to increase the productivity of red beans and quality which has a main component consisting of frame, peeler roll, inlet, outlet and motor drive. While the supporting components are reducer, fan, bearing, pully, belt, chain, and main shaft. The types of machine tools used are lathes, cutting grinding machines, hand grinding machines, welding machines, drilling machines, sawing machines, milling machines and cylindrical grinding machines. Some things that need to be considered from the manufacture of red bean peeling machines are identifying materials and models, choosing machine tools, planning work steps, analyzing the processing time and making a schedule for making red bean skin peeling machines. From the results of the analysis of the calculation of the work that can be analyzed perole the total time of making components is 23.58 hours.